1971
DOI: 10.1073/pnas.68.4.851
|View full text |Cite
|
Sign up to set email alerts
|

The Synaptinemal Complex and Four-Strand Crossing Over

Abstract: The synaptinemal complex provides a structural basis for four-strand crossing over: prior to chromosome pairing, both sister chromatids of each homologous chromosome participate in the genesis of one lateral component. During precise pairing, the two lateral components are combined into one synaptinemal complex per bivalent.THE SYNAPTINEMAL COMPLEX

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…This pairing mechanism is identical to the one proposed by WESTERGAARD & VON WETTSTE1N (61,63) and proven by vON WETTSTEIN (64) through reconstruction of a zygotene nucleus in Neottiella. It implies that the central region cannot be an integral part of the zygotene chromosome or the lateral component as often proposed (8,9,37).…”
Section: Chromosome Alignment and Pairingsupporting
confidence: 53%
See 2 more Smart Citations
“…This pairing mechanism is identical to the one proposed by WESTERGAARD & VON WETTSTE1N (61,63) and proven by vON WETTSTEIN (64) through reconstruction of a zygotene nucleus in Neottiella. It implies that the central region cannot be an integral part of the zygotene chromosome or the lateral component as often proposed (8,9,37).…”
Section: Chromosome Alignment and Pairingsupporting
confidence: 53%
“…STERN & HOTTA (54) favour the hypothesis that pairing is specified at the DNA level through matching of homologous regions of zygotene-DNA, followed by alignment and ultimate organization of the synaptinemal complex via the formation of the central region. WESTERGAARD & VON WETTSTEIN (61,62) and VON WEYrSlEIN (63,64) suggested that homologous chromosomes are roughly aligned by some unknown mechanism and that the required specificity for pairing was housed in the form of RNA and protein in the lateral components. It was hypothesized (63) that by binding of the central region to one of the lateral components a series of conformational changes was induced in the unspecific central region, which created a specificity on the opposite surface of the central region matching the lateral component of the homologous chromosome.…”
Section: Chromosome Alignment and Pairingmentioning
confidence: 99%
See 1 more Smart Citation
“…Vol. 43, p. [423][424][425][426][427][428][429][430][431][432][433][434][435][436][437][438]1978 chromatin bridges (20,24,26). Retained synaptonemal complex fragments have, however, been reported in the grasshopper, Corthippus longicornis (12), in the pigeon (15), and in human spermatocytes (7,21), either in the form of small fragments of apparently normal synaptonemal complexes or as small aggregates of rearranged synaptonemal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it was noted that the short arms of the acrocentric bivalents were virtually devoid of chiasmata while a chiasma was present between the sex chromosomes in 63% of the nuclei. The discrepancy between the mean number of nodules (75) at early pachytene and the mean number of chiasmata (50) may be attributed to the inherent difficulties in the light microscopical analysis to resolve two or more closely positioned chiasmata or it may be due to a terminalization of chiasmata. The observation that terminal chiasmata are frequent at diakinesis while the telomere region at early pachytene is only slightly enriched in nodules is in support of the latter possibility.…”
mentioning
confidence: 99%